2014
DOI: 10.21273/hortsci.49.4.486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substrate Water Content on Morphology and Physiology of Rosemary, Canadian Columbine, and Cheddar Pink

Abstract: Two experiments were conducted to determine how different substrate volumetric water contents (θ equals volume of water per volume of substrate) affected morphology and physiology of three popular perennials using a capacitance sensor-automated irrigation system. In the first study, rosemary (Rosmarinus officinalis) was grown at one of eight θ set points ranging from 0.05 to 0.40 L·L−1. In the second study, Canadian columbine (Aquilegia canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 27 publications
(49 reference statements)
5
19
0
Order By: Relevance
“…The growth and development of containerized basil, dill, parsley, and sage is promoted with increasing substrate VWC. While the effect of substrate moisture on growth is better understood for containerized ornamental flowering crops, our results on the effect of substrate VWC on controlling growth of culinary herbs align well with the limited literature on container-grown herbs, including rosemary and English lavender [8,9]. For example, Zhen et al [8] reported that, as substrate VWC increased from 0.05 to 0.40 m 3 ·m −3 , the height, width, leaf number and area, and fresh and dry mass of rosemary increased linearly.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The growth and development of containerized basil, dill, parsley, and sage is promoted with increasing substrate VWC. While the effect of substrate moisture on growth is better understood for containerized ornamental flowering crops, our results on the effect of substrate VWC on controlling growth of culinary herbs align well with the limited literature on container-grown herbs, including rosemary and English lavender [8,9]. For example, Zhen et al [8] reported that, as substrate VWC increased from 0.05 to 0.40 m 3 ·m −3 , the height, width, leaf number and area, and fresh and dry mass of rosemary increased linearly.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, restricting P to 5 mg·L −1 produced basil, dill, parsley, and sage shorter than plants provided with 40 mg·L −1 [5]. While cultivar selection and nutrient management are useful forms of nonchemical growth control, it may be necessary to use multiple nonchemical methods of controlling growth to achieve the degree of control required in the absence of PGRs.Reducing irrigation or substrate volumetric water content (VWC), commonly referred to as "deficit irrigation", is another effective method of controlling containerized plant growth [6][7][8]. The water available for plant uptake increases and growth is promoted as substrate VWC increases and, as such, restricting irrigation and reducing the substrate VWC can diminish turgor pressure and subsequent stem extension and growth [9].…”
mentioning
confidence: 99%
See 3 more Smart Citations